Strange Children - Hoagland, Sadie (Book collections on Project MUSE., 2021)
"In a polygamist commune in the desert, a fourteen-year-old boy and a twelve-year-old girl fall in love and consummate that love, breaking religious law. They are caught, and a year later, she gives birth to his father's child while the boy commits murder four hundred miles away--a crime that will slowly unravel the community. Told by eight adolescent narrators, this is a story of how people use faith to justify cruelty, and how redemption can come from unexpected places. Though seemingly powerless in the face of their fundamentalist religion, these 'strange children' shift into the central framework of their world as they come of age"--